Informed Citizen Panels on the Swiss Electricity Mix 2035: Longer-Term Evolution of Citizen Preferences and Affect in Two Cities - Alexane Dubois; Simona Holzer; Georgios Xexakis; Julia Cousse; Evelina Trutnevyte (Energies, 2019)
For a successful transition to low-carbon electricity supply, public support is essential. Citizen preferences are best understood in the process of informed citizen panels, where citizens are informed about the pros and cons of various electricity technologies and spend time reflecting on the trade-offs. We investigated how information about electricity technologies and their sustainability impacts can change citizens’ preferences and affect for the complete Swiss electricity mix 2035. The citizens received information as factsheets and, during workshops, discussed in groups and built their preferred electricity mix using an interactive tool. The informed citizen panel (N = 33) in the Swiss city of Geneva showed high support for domestic renewable technologies and end-use efficiency, as well as low support for net electricity import, natural gas, and nuclear power. Preferences and affect for unfamiliar technologies changed after receiving information and remained stable even in the longer term four weeks after. Preferences and affect for already familiar technologies, like hydropower, barely changed. The same procedure in the two Swiss cities of Geneva and Zurich (N = 46) enabled the identification of robust support for renewable technologies and efficiency with only minor context-specific differences.